Determination of 21 antibiotics in sea cucumber using accelerated solvent extraction with in-cell clean-up coupled to ultra-performance liquid chromatography-tandem mass spectrometry. (30th August 2018) - Zhu, Minghua; Zhao, Hongxia; Xia, Deming; Du, Juan; Xie, Huaijun; Chen, Jingwen
Highlights: A reliable method for analysis of 21 antibiotics in sea cucumber was developed. The method was based on ASE with in-cell clean-up and UPLC-MS/MS. The method was validated and compared to the reported USE method. This is a simple, time- and solvent-effective method. Abstract: An accelerated solvent extraction (ASE) with in-cell clean-up method coupled to ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) was developed to determine 21 antibiotics in sea cucumber. The analytes include 10 sulfonamides, 4 fluoroquinolones, 3 amphenicols, 2 beta-lactams, 1 lincosamide and trimethoprim. Optimal parameters of ASE method were obtained at 80 °C, 1 static cycle of 5 min with methanol/acetonitrile (1/1, v/v) using 2 g of C18 as adsorbent. Recoveries at 50.1–129.2% were achieved with RSD under 20%. Method detection limits ranged from 0.03 to 2.9 μg kg −1 . Compared to the reported ultrasound-assisted extraction method, the proposed method offered comparable extraction efficiency for sulfonamides from sea cucumber, but higher for other categories of antibiotics. This validated method was then successfully applied to sea cucumber samples and 9 antibiotics were detected with the highest concentration up to 57.7 μg kg −1 for norfloxacin.